On pragmatism, assemblage and ANT: Assembling reason. (June 2021) - Bridge, Gary
In geography the key theoretical registers of assemblage theory and Actor Network Theory have been psychoanalytic-semiotic, materialist and vitalist (emphasising affect). In contrast, this paper indicates the original influence and continued relevance of philosophical pragmatism's action-oriented approach for assemblage and ANT. It suggests how a pragmatist understanding of human experience, situation and reason offers a different perspective on the nature of emergent and relational space in assemblages and networks. This perspective extends existing pragmatist work in geography to explore the distinctive, hyper-relational spatialities of human activity in a world of acting things, suggesting wider implications for progress in human geography.